2006
DOI: 10.1007/s00248-005-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Yeasts and Grapevines: Filamentous Growth, Endopolygalacturonase and Phytopathogenicity of Colonizing Yeasts

Abstract: It has been clearly established that phytopathogenic fungi, bacteria, and viruses exert biotic stresses on plants. Much less is known, however, about the interactions between enological species of yeast and their host plants. In a previous study, we described how Saccharomyces cerevisiae, the most common enological yeast, can act as a grapevine (Vitis vinifera L.) pathogen, causing growth retardation or plant death. In the present in vitro study on 11 strains of yeast belonging to different genera, which often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Scale bar: 10 lm. In 3, haploid industrial strain CCA022 growing on YEPD medium without (a) and with (b) 0.5% isoamyl alcohol, scale bar: 6 lm; haploid industrial strain CCA037 growing in liquid YEPD medium without (c) and with (d) 0.5% isoamyl alcohol, scale bar: 5 lm (Reprinted from Lorenz et al 2000 (1a, b); Silva et al 2007 (1c, d, 2a-d, 3a, b); Vancetto et al 2007 (3c, d), with permission) after an in vitro study on 11 strains of yeast from different genera, including S. cerevisiae, often occurring on the surfaces of vineyard grapes and V. vinifera (Gognies et al 2006).…”
Section: Functional and Biotechnological Significance Of Filamentatiomentioning
confidence: 93%
See 2 more Smart Citations
“…Scale bar: 10 lm. In 3, haploid industrial strain CCA022 growing on YEPD medium without (a) and with (b) 0.5% isoamyl alcohol, scale bar: 6 lm; haploid industrial strain CCA037 growing in liquid YEPD medium without (c) and with (d) 0.5% isoamyl alcohol, scale bar: 5 lm (Reprinted from Lorenz et al 2000 (1a, b); Silva et al 2007 (1c, d, 2a-d, 3a, b); Vancetto et al 2007 (3c, d), with permission) after an in vitro study on 11 strains of yeast from different genera, including S. cerevisiae, often occurring on the surfaces of vineyard grapes and V. vinifera (Gognies et al 2006).…”
Section: Functional and Biotechnological Significance Of Filamentatiomentioning
confidence: 93%
“…For Vitis vinifera, the pseudohyphal growth was necessary for yeasts to colonize plant tissues (Gognies et al 2006). The finding that indole acetic acid, a plant hormone, triggers pseudohyphal growth in S. cerevisiae (Prusty et al 2004) suggests a plant-yeast interaction, mediated by plant-derived signals, in which filamentation may play an important role.…”
Section: Final Considerations and Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…There are various yeast species described as pathogenic for table grapes being Pichia, Brettanomyces, Cryptococcus, and Rhodotorula the most studied (Gognies et al, 2006). Even Saccharomyces cerevisiae, the most researched fermentative yeast, can also act as a pathogen on plants causing delay in their growth or death (Gognies et al, 2001).…”
Section: Yeast Pathogenicity On Table Grape Berriesmentioning
confidence: 99%
“…Otherwise, analysis of expression has shown that the PGL1p activity by degradation of pectin could play another function. Thus, it was reported that the PGL1 gene was a target of the MAPK regulatory pathway and was also required in pseudohyphae development [30] and therefore involved in plant pathogenesis [14,15,18].…”
Section: Introductionmentioning
confidence: 98%